CONSUMER REPURCHASE INTENTION MODEL IN LAZADA E-COMMERCE - Harisatul , Agustin; Dewie Saktia , Ardiantono; Tavia Adinta , Shalati (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2023)
The emergence of technology and the Internet has significantly influenced the use of digital platforms, especially in the realm of online commerce or e-commerce. One of the e-commerce in Indonesia is Lazada. Lazada consistently improves its sales techniques to remain competitive, including through consumer reviews communicated via Electronic Word of Mouth (E-WOM). This research analyzes the influence of sales promotions, brand recognition, and perceived ease of use on purchasing decisions and intentions to make repeat purchases. This study uses a quantitative approach. The population in this study was Lazada consumers in Jakarta, Bogor, Depok, Tangerang, Bekasi, and the sample used was 337. Analysis was carried out using SmartPLS software. The results show that sales promotions, brand recognition, and perceived ease of use benefit purchasing decisions, influencing consumers' intentions to make repeat purchases. Consumer trust has a significant role in influencing the relationship between purchasing decisions and repurchase intentions. However, electronic word-of-mouth (E-WOM) does not significantly influence purchasing decisions within Lazada's e-commerce framework.